2014
DOI: 10.1371/journal.pone.0086072
|View full text |Cite|
|
Sign up to set email alerts
|

Spatio-Temporal Patterns of Beaked Whale Echolocation Signals in the North Pacific

Abstract: At least ten species of beaked whales inhabit the North Pacific, but little is known about their abundance, ecology, and behavior, as they are elusive and difficult to distinguish visually at sea. Six of these species produce known species-specific frequency modulated (FM) echolocation pulses: Baird’s, Blainville’s, Cuvier’s, Deraniyagala’s, Longman’s, and Stejneger’s beaked whales. Additionally, one described FM pulse (BWC) from Cross Seamount, Hawai’i, and three unknown FM pulse types (BW40, BW43, BW70) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 61 publications
7
87
0
Order By: Relevance
“…Temporal coverage was limited to a single year or included substantial gaps at several of our monitoring sites, and data from additional years may be necessary to reveal subtler seasonal or interannual trends. However, results from large-scale PAM in the North Pacific demonstrated a similar lack of temporal patterning in the detection of beaked whale acoustic signals (Baumann-Pickering et al 2014), and coordinated seasonal movements have not been documented in any beaked whale species. Studies utilizing photographic identification or animal-borne satellite telemetry tags have revealed a high degree of site fidelity within some beaked whale populations, including Cuvier's and Blainville's beaked whales in Hawai'i (McSweeney et al 2007;Schorr et al 2010), Blainville's beaked whales in the Bahamas (Claridge 2013), and northern bottlenose whales in Nova Scotia (Hooker et al 2002;Wimmer and Whitehead 2004).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Temporal coverage was limited to a single year or included substantial gaps at several of our monitoring sites, and data from additional years may be necessary to reveal subtler seasonal or interannual trends. However, results from large-scale PAM in the North Pacific demonstrated a similar lack of temporal patterning in the detection of beaked whale acoustic signals (Baumann-Pickering et al 2014), and coordinated seasonal movements have not been documented in any beaked whale species. Studies utilizing photographic identification or animal-borne satellite telemetry tags have revealed a high degree of site fidelity within some beaked whale populations, including Cuvier's and Blainville's beaked whales in Hawai'i (McSweeney et al 2007;Schorr et al 2010), Blainville's beaked whales in the Bahamas (Claridge 2013), and northern bottlenose whales in Nova Scotia (Hooker et al 2002;Wimmer and Whitehead 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Prior studies have shown that many beaked whale species produce a stereotyped echolocation signal type that is stable across geographic regions (Baumann-Pickering et al 2014). However, we acknowledge that scientific understanding of the acoustic behavior of most beaked whale species is far from complete, particularly for True's, Sowerby's, and Gervais' beaked whales in the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One manuscript on world-wide beaked whale descriptions was published (Baumann-Pickering et al, 2014), and three more have been submitted (Roch et al, submitted-a; Roch et al, submitted-b; Širović et al, submitted Roch et al (submitted-b) is an echolocation click classification study that examined the effects of equipment and site variability across a range of instruments and years in the Southern California Bight. Analyses conducted in the three studies were greatly simplified by the use of the Tethys Metadata Workbench.…”
Section: Resultsmentioning
confidence: 99%
“…Back then, the researchers had to actually see a marine mammal to make recordings, dipping underwater microphones, called hydrophones, a few meters into the water. It wasn't until the 1990s that biologists started experimenting with autonomous recording devices that could be left out at sea (2).…”
Section: An Emerging Fieldmentioning
confidence: 99%